Applying Fluorescence Dissolved Organic Matter Spectra and Phytoplankton Biology Index for Assessing Urban River Quality - Okik Hendriyanto Cahyonugroho; Sucipto Hariyanto; Ganden Supriyanto (Directorate for Research and Community Services (LPPM) ITB, 2023)
The relationship between phytoplankton dynamics and dissolved organic matter (DOM) in aquatic systems based on fluorophore organic matter properties results in poor implementation of methods for water quality monitoring. This study aimed to investigate the relation between fluorophore organic matter and phytoplankton index and to estimate the phytoplankton index by fluorescent organic components for water quality assessment. The research was conducted by sampling urban river water, followed by measuring the biological phytoplankton index and dissolved organic matter during the wet and dry seasons. Fluorescence Excitation Emission Matrices (FEEMs) analysis combined with Parallel Factor (PARAFAC) analysis identified three main components of the fluorescence organic matter, i.e., a fulvic acid-like component (C1) and humic acid-like components (C2 and C3), in the aquatic system, whether in the dry season or the wet season. C1 was mainly generated by phytoplankton species, i.e., Nitzschia sp., Plectonema sp., Navicula sp., and Pinnularia sp., and C2 and C3 had a less signiﬁcant relationship with phytoplankton species. The diversity of Bacillariophyta had a stronger contribution to the release of DOM than the diversity of Cyanobacteria. The abundance index of a particular phytoplankton species can be used to determine the organic components of FEEM-derived fluorescence organic matter.